Projeto Construindo e Desafiando a Produtividade (CDP): um estudo de caso - Gutheil, Antonio Luiz Martins (2023)
Direct planting reduces the emission of greenhouse gases, which is very positive for the planet. This is due to the fact that this system is widely used for the production of grains in Brazil, such as beans, soybeans, corn, rice and wheat. Such productions do not require soil preparation, greatly reducing gas emissions. The current generation of agricultural producers reaps the fruits of the continuous search for science when it comes to diagnosing and treating only existing problems, always in the most correct way possible. Today, the best way to be assertive and correct in the management of agricultural areas is to adopt the so-called Production Environments (high, medium and low fertility zones), with the aim of knowing the factors that make up the formation of a given soil and its water interactions, physical, chemical and/or morphological with the vegetation cover. Thus, this work aimed to evaluate the spatial variability of the different production environments, crossing certain data to obtain good diagnoses, prognoses and transform data into information that can be used for decision making. This management aimed at improving the areas in order to deal with a situation in space and time, that is, to delimit regions to be more assertive. Thus, the understanding and application of the different production environments are differentiated to achieve sustainability and leverage profitability for the producer. The Study was conducted from the 2017 agricultural year until 2021 in the 13 areas participating in the Building and Challenging Productivity Project. The analyzes were carried out in no-tillage areas, distributed in 13 municipalities in the North of RS.